2019
DOI: 10.1097/md.0000000000017574
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom intoxication, a fatal condition in Romanian children

Abstract: Rationale:Approximately 5000 species of wild mushroom are reported worldwide, of which 100 are documented as poisonous and <10 are fatal. The clinical picture of patients with wild mushroom intoxication depends mostly on the type of ingested mushroom, ranging from mild gastrointestinal symptoms to organ failure and death.Patient concerns:We report 2 children, sister and brother admitted in our clinic for gastrointestinal symptoms: abdominal pain, nausea, vomiting, and diarrhea after wild mushroom ingestion.Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this study, however, more than half of the patients reported GI symptoms; additionally, non-specific symptoms, such as general weakness, were prevalent, causing difficulty in the identification of cases according to the clinical symptoms. In some previous studies, diarrhea was found to cause dehydration and severe renal failure [10,29]. In this study, diarrhea was not related to admission.…”
Section: Discussionsupporting
confidence: 46%
“…In this study, however, more than half of the patients reported GI symptoms; additionally, non-specific symptoms, such as general weakness, were prevalent, causing difficulty in the identification of cases according to the clinical symptoms. In some previous studies, diarrhea was found to cause dehydration and severe renal failure [10,29]. In this study, diarrhea was not related to admission.…”
Section: Discussionsupporting
confidence: 46%
“…In extreme cases, the sole option for survival may be a liver transplant, which is occasionally either not possible or medically problematic. Dialysis may be necessary if renal insufficiency is severe [ 5 , 14 ]. Patients with liver failure must be moved as soon as possible to a hospital that has a liver transplantation center.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture of patients with wild mushroom intoxication depends mainly on the type of ingested mushroom, which can range from minor gastrointestinal symptoms, such as abdominal pain, nausea, vomiting, and diarrhea, to organ failure and death. Hepatotoxicity and liver failure are associated with a small group of mushrooms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, a special role was played by the observance of the mating matching system, specific to the studs, to avoid inbreeding. Marginean et al (2005Marginean et al ( , 2012 and Maftei et al (2012 shows that the kinship between individuals directly influences the increase of homozygosity.…”
Section: Introductionmentioning
confidence: 99%